Indigenous entrepreneurship: Closing the gap on local terms - Brueckner, Martin; Pearson, Cecil; Chatterjee, Samir; Wise, G.; Marika, B. (Society for Global Business & Economic Development (SGBED), 2011)
Australian federal government policy over the last ten years has renewed the focus on closing the gap between Indigenous and non-Indigenous Australians, targeting chiefly improvements in health and economic participation among Indigenous people. Thus far, however, the results have been mixed, in part because of the endurance of Indigenous socio-economic disadvantage in Australia which cannot be expected to be undone within a matter of years. Failure to deliver better policy outcomes, however, can also be seen as a function of an inflexible policy design, which aims at the mainstreaming of Indigenous communities on non-Indigenous terms, whilst militating against the potential for Indigenous entrepreneurial activities especially in rural and remote regions.Against this policy background, this paper reports on local entrepreneurial activities by local Yolngu clans in East Arnhem Land in the Northern Territories (NT). In particular, attention is directed to local for-profit and not-for-profit activities by members of the Gumatj clan south of the regional centre of Nhulunbuy and the Rirratjingu operations in the town Yirrkala respectively. The paper describes how the ventures run by the Gumatj and Rirratjingu clans offer pathways for the creation of income, employment and social capital within the respective local communities whilst also being axiomatic in the protection of cultural vitality and integrity. The findings point to the need for more flexible approaches to policy design and delivery, enabling the establishment and growth of Indigenous business activities outside the economic mainstream targeted by federal government policy. As such, the authors echo calls in the literature for policy support for what has been described as the 'hybrid economy', which allows for participation in both economic and cultural activities both of which are crucial for Indigenous future well-being as they are for any cultural group.